Pengembangan Buku Saku (E-Media) Termodinamika Berorientasi Android - Andi Putra Sairi (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2018)
Completing the teaching material is a task that must be carried out by the lecturer when carrying out pedagogical and pedagogical activities. A good learning tool is an element that must exist and must always be developed in order to improve the quality of learning in universities, such as learning materials. Indeed, the learning medium itself is a tool used to transmit knowledge to students in order to overcome the limitations of the senses, time and space. In addition, the availability of learning materials should also follow the evolution of the science and technology that is developing at this time. On this basis, efforts should be made to develop an educational resource in the form of an effective " pocket book " that will serve as a pedagogical medium for students to overcome the problems they face. Therefore, the purpose of this study is to describe the design, validity, and efficiency of using a thermodynamic paperback for Android. This research is a research and development (R & D) with the model used in this development is the development model of the model 4-D (model Four D). These steps are definition, design, development and propagation (desimination). The results showed that the Android-oriented thermodynamic pocket book (e-media) was very valid, very practical and effective for learning activities.